Electronic band structure of ZnSe(100) - Dröge, H.; Nagelstraßer, M.; Nürnberger, J.; Faschinger, W.; Fleszar, A.; Steinrück, Hans-Peter (Surface Science, 2000)
The k-resolved band structure of an epitaxially grown ZnSe(100) layer was investigated by angle resolved ultraviolet photoelectron spectroscopy combined with ab initio band structure calculations. The ZnSe layer 4 μm thick was grown on a GaAs(100) substrate by molecular beam epitaxy and was transported to the German synchrotron facility BESSY under ultrahigh vacuum (UHV) conditions using a specially designed UHV transport box. The dispersion of the valence bands was measured along the ΓX direction using photon energies between 15.2 and 44 eV. The experimental results are analyzed using the free-electron approximation as well as the calculated ZnSe bulk band structure for the final states.